Addressing Debt Vulnerabilities in Small States : The Potential Role of New Financing Instruments - Haque, Tobias; Partow, Zeinab; Varma, Sona; Oliveira, Luiz Edgard (World Bank, Washington, DC, 2016)
The papers in this series aim to provide a vehicle for publishing preliminary results on Macroeconomics and Fiscal Management (MFM) topics to encourage discussion and debate. This paper explores two new financing mechanisms that multilateral and bilateral development agencies could consider deploying to address problems of debt sustainability in small states. In this paper the authors provide an initial assessment of these proposals, informed by analysis of small state indebtedness and recent debt dynamics. Proposed financing instruments are predicated on assumptions that small states face high levels of indebtedness, and that reducing debt levels while increasing climate resilience could sustainably reduce such vulnerabilities. The authors find that levels of indebtedness vary widely across small states. Analysis of small state debt dynamics shows that small state debt accumulation has been driven by large primary and current account deficits and slow economic growth. Debt reduction from new mechanisms can only be expected to be sustainable, therefore, if countries simultaneously address the macroeconomic imbalances driving debt accumulation. The authors demonstrate that, while exposure to natural disasters is likely to have exacerbated economic management challenges in some small states, such exposures are unlikely to be the only important cause of indebtedness. The authors conclude that proposed new financing instruments can potentially help reduce small state debt burdens and gain fiscal space for climate adaptation but will not present a sustainable solution to problems of small state debt risks unless they involve macroeconomic and structural reforms to address the underlying imbalances driving rapid debt accumulation.